Implementasi Data Mining Untuk Mengklasifikasikan Produk Pada Sebuah Supermarket Mengunakan Algoritma ID3 Pada Orange - Nengah Widya Utami; I Wayan Budi Suryawan (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2021)
Technological developments are increasingly increasing or developing very rapidly. The development of technology has also affected the increasing needs of the community, so supermarkets and retailers are competing to provide various types of products or daily needs. However, in every collection or supermarket, it is necessary to know what types of products are needed by customers who will later become targets. To help shops and supermarkets, the authors will conduct an analysis to find out the types of products that customers like by implementing data mining in supermarket classification using the ID3 algorithm